Managing the professional service firm - Maister, David H. (New York : Free Press Paperback, 1993)
Explores issues such as marketing, business development, multinational strategies, human resource policies, profit improvement, strategic planning and effective leadership.
Keywords: Management; Διοίκηση και οργάνωση.